ANALISIS PENGELOLAAN KEUANGAN DAERAH DI KABUPATEN SAMBAS - Yuman Firmansyah; Zainal Amaluddin; Abdul Ghofur; Raharjo Raharjo (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2025)
This study aims to identify and analyze regional financial management in Sambas Regency for 5 years from 2017 to 2021. The main focus of this study is to evaluate the effectiveness of regional government financial performance through financial ratio analysis, analysis of the realization of regional revenue and expenditure budgets (APBD). The method used in this study is a qualitative descriptive approach with regional financial management analysis techniques in Sambas Regency. Based on the descriptive qualitative approach, several main findings were found such as low human resource capacity, weak internal control systems, and inaccuracy in budget planning. The results of this study indicate that the liquidity ratio consisting of an average current ratio of 0.82 means that every Rp. 1, - current debt is guaranteed by Rp. 0.82, - current assets, an average cash ratio of 0.35 means that every Rp. 1, - current assets of Rp. 0.35 are cash and cash equivalents; cash to current liabilities average of 0.29 means the ability of the Regional Government to pay immediately every Rp.1- current debt using cash and equivalents of Rp.0.29,- average quick ratio of 0.60 means that the ability of the Regional Government to meet short-term obligations for every Rp.1,- using cash, cash equivalents and receivables. Of Rp.0.60, the average cash flow ratio of 2.31 means the ability of a Regional Government's operating cash flow to pay every Rp.1,- current debt owned using operating cash of Rp.2.31,-; the leverage ratio measured is the short-term debt to long-term debt ratio of 1.00. Based on the research presentation above, the researcher recommends the need to improve the competence of regional financial management apparatus through continuous training, strengthening digital-based financial management information systems and optimizing the role of the regional inspectorate as an internal supervisory institution. It is hoped that there will be improvements by the Regional Government in the coming year to ensure that the Debt Service Coverage Ratio (DSCR) remains at the minimum limit outlined by the Central Government because if loans continue to increase, there is concern that the Sambas Regency Regional Government will not be able to meet mandatory expenditure as regulated in PP 30/2011 concerning regional loans in Article 15 paragraph (1) letter b. Keywords : Analysis, Regional Financial Management, Sambas Regency Government.